Determination of the effect of Hypericum perforatum oil supplementation on silage quality in ruminant feeding - Arslan Duru, A (Journal of the Hellenic Veterinary Medical Society, 2024)
This study evaluated the effect of Hypericum perforatum oil (HPO) on chemical composition, fermentation traits and metabolic energy, in vitro organic matter digestibility, and net energy lactation of Hungarian vetch-wheat silages. The treatments were: (i) control (No HPO), (ii) 20 mg/kg HPO, (iii) 40 mg/kg HPO, (iv) 80 mg/kg HPO and (v) 160 mg/kg HPO in Hungarian vetch-wheat silages. After 75 days of ensiling, dry matter, NDF and ADF were increased by adding 20 mg/kg and 40 mg/kg Hypericum perforatum oil to Hungarian vetch-wheat silage (p<0.01). However, there was no significant in the content of silage in lactic acid, acetic acid, propionic acid, metabolic energy, in vitro organic matter digestibility, and net energy lactation (p>0.05). Butyric acid and ammonia nitrogen were not found in the experiment silages. Finally, it was concluded that the addition of 20 mg/kg Hypericum perforatum oil may have a positive effect on the quality of Hungarian vetch-wheat silages.